Mulberry leaf polysaccharide supplementation contributes to enhancing the respiratory mucosal barrier immune response in Newcastle disease virus–vaccinated chicks - Xiaolan Chen; Haifeng Yang; Jiping Jia; Yu Chen; Jing Wang; Haifeng Chen; Chunmao Jiang (Poultry Science, 2021)
Despite high global vaccination coverage, Newcastle disease (ND) remains a constant threat to poultry producers owing to low antibody levels. Given the respiratory mucosa is the important site for Newcastle disease virus (NDV) vaccination, enhancing respiratory mucosal immunity may help control ND. Our previous study showed that mulberry leaf polysaccharide (MLP) is very promising in delivering a robust balanced immune response, but the effects of it on respiratory immunity in chicks are unknown. In this study, we evaluated the potential of MLP to activate respiratory mucosal immunity and revealed the possible mechanism of MLP as an immunopotentiator for ND vaccines. Chicks were randomly divided into 5 groups: blank control, vaccination control (VC), and low-, middle-, and high-dose MLP (MLP-L, MLP-M, and MLP-H) (n = 30). The serum results of humoral and cell-mediated immune responses showed significant increases in NDV hemagglutination inhibition antibody titer, IgG and IgA antibody levels, and the T-lymphocyte population in the MLP-M group compared with the VC group. Validation of results also indicated remarkable increases in tracheal antibody-mediated immunity and a mucosal immune response in the MLP-M group. Furthermore, the upregulation of TLR7 revealed a possible mechanism. Our findings provided evidence to consider MLP as a potential mucosal vaccine adjuvant candidate against ND in chickens.